The presence of Swift in Slovene translation and commentary - Stubbs, John (ELOPE (Ljubljana), 2024)
Although the Slovene milieu has yet to afford Swift’s works a multi-volume critical translation of the kind available in other European languages, this paper argues that Slovene representations of Swift’s writings illuminate crucial aspects of his meaning. This can be seen especially in Mladen Dolar’s afterword to a new unabridged translation of Gulliver’s Travels, in which he approaches Swift through a versatile and profoundly contemporary – yet still accessible – conceptual vocabulary, and in the first Slovene translation of Swift’s Modest Proposal, which retains and transmits the original’s power as a political act. The essay surveys the enduring international presence of Swift in translation and translation studies, outlines aspects of translation theory that prove relevant to its own inquiry, and proceeds to consider the Slovene contribution to Swift’s legacy.
Keywords: Dolar, Mladen; glas; Mahkota, Tina; Mladina; paralaksa; parallax; prevod; Swift, Jonathan; translation; voice